How does herd behaviour impact the purchase intention? Explore the moderating effect of risk aversion in the context of Vietnamese consumers - Minh Pham; Nhu Kieu Thi Vo; Sang Sang Thi Tran; Huy Hoang Tran To; Bao Quoc Lam (Acta Psychologica, 2023)
Managers have been applying the influence of herd behaviour to stimulate purchase intention but have not achieved precise results because they do not clearly understand the mechanism of this relationship. This article aims to determine the effect of herd behaviour on the relationship between information adoption and purchase intention and the moderating of risk aversion. With 17 variables for four concepts, data was collected online with 340 respondents and analysed with a partial least squares structural equation modelling. When considering herd behaviour in terms of subjective norms with corroborated information, this study upgrades the classic role of the theory of planned behaviour in purchase intention. The findings indicate a positive relationship between herd behaviour, information adoption and purchase intention. In particular, risk aversion is a positive moderator of the relationship between herd behaviour and purchase intention. This result is a significant addition to the theoretical body and shows that risk aversion can drive purchase intention through herd behaviour. In other words, this study upgrades the perception of information source authentication through herd behaviour to explain the purchase intentions of Vietnamese consumers. These results show that managers can create risky situations to promote herd behaviour. They can also apply information adoption stimuli to stimulate herd behaviour. At the same time, through the information adoption mechanism, consumers can be more alert to the effect of herd behaviour and have more opinions when making purchases.